PERFORMANCE RELATIONS OFFICER WITH QUALITY HEALTH CARE HEALTH SERVICES IN HEALTH CENTERS - SUHARTIK, SUHARTIK; HIDAYAH, WAQIDIL; Susanti, Aprilia Heri (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2015)
AbstractGood performance is generated if there is communication between all healthcare workers to form internalization within a strong organizational culture and understood in accordance with the organizational values that can lead to a positive perception among all levels of employees. The purpose of this study was to determine the relationship of performance of health care workers with quality health services at the health center. The study design used is analytic approach secsional Cross. The population of all health care workers in health centers Kedewan Kedewan District of Bojonegoro in 2014 with 20 people with a total sampling. Collecting data for the independent variables using a questionnaire and then analyzed using statistical test Chi - square. Based on the survey results revealed that of the 20 respondents, the officer has assessed the performance of 55%, quality 60% and 66.7% cross tabulation results with ? value of 0.05 is obtained ? = o, 299 <?. So the known value of Ho is accepted. The conclusion of this study is there is no relationship between the performance of health care workers with quality health services in the District Health Center Village Kedewan Kedewan Bojonegoro. So advised the respondent to cooperate in maintaining and improving the quality of performance, and improve the quality to be better. Keywords: performance, personnel, quality of service